Foot Massage Berpengaruh Terhadap Nyeri Pada Pasien Dengan Post Sectio Caesarea Di Ruang Jade RSUD Dr Slamet Garut: Studi Kasus - Azizah, Puput Nur; Hermayanti, Yanti; Mamuroh, Lilis (Nursing News : Jurnal Ilmiah Keperawatan, 2023)
Section Cesarea (SC) is a method of delivering a fetus through an abdominal incision (laparotomy) and an incision in the uterus (hysterotomy). The problem that most often occurs in post-SC mothers is pain. Foot massage produces impulses that are sent through nociceptor afferent nerve fibers which make the gates close so that the pain stimulus is blocked. The aim of this study was to identify the effect of foot massage on pain in post-SC mothers in the Jade room at Dr. Slamet Hospital, Garut. The research design used is descriptive with a case study method. The research was conducted in the Jade room at Dr. Slamet Hospital, Garut. The number of participants was one client who experienced post SC for indications of placenta previa and former SC. Data was collected from the results of the assessment using the postpartum assessment format from the Department of Maternity, Faculty of Nursing, Padjadjaran University and the Numeric Rating Scale to assess pain. The results of the case study showed a decrease in the pain scale felt by the mother after SC where the pain scale before the foot massage intervention was 7/10 and after the foot massage intervention the pain scale decreased to 4/10. Thus, Foot Massage has an influence on reducing the pain scale in Post SC mothers in the Jade room at Dr. Slamet Hospital, Garut. Foot massage can be an alternative non-pharmacological management that can be carried out by nurses to reduce pain in post-SC mothers. Suggestions for future researchers are expected to use experimental research methods to reduce bias.